2009
DOI: 10.1158/1055-9965.epi-09-0241
|View full text |Cite
|
Sign up to set email alerts
|

Association of Colorectal Cancer and Prostate Cancer and Impact of Radiation Therapy

Abstract: To quantify the risk of prostate cancer after colorectal cancer and the risk of colorectal cancer after prostate cancer and to examine the impact of radiation therapy on subsequent cancer risk, we conducted retrospective cohort studies using data from the Surveillance, Epidemiology and End Results program from 1973 to 2005. Standardized incidence ratios (SIR) and 95% confidence intervals (95% CI) were calculated, adjusting for age, ethnicity, and calendar year. The subsequent risk of developing a prostate canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 28 publications
(40 reference statements)
1
38
0
Order By: Relevance
“…Since the rectum and bladder are definitively considered irradiated fields during RT for prostate cancer, it is reasonable that these tissues will receive more radiation dosage than other parts of the human body. However, in the subgroup analysis, no significantly increased secondary malignancy risk was observed; this is consistent with most studies [13,14,17,18,19,20]. Similarly, relevant parts of the bladder also receive radiation doses.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Since the rectum and bladder are definitively considered irradiated fields during RT for prostate cancer, it is reasonable that these tissues will receive more radiation dosage than other parts of the human body. However, in the subgroup analysis, no significantly increased secondary malignancy risk was observed; this is consistent with most studies [13,14,17,18,19,20]. Similarly, relevant parts of the bladder also receive radiation doses.…”
Section: Discussionsupporting
confidence: 89%
“…Hand-searching the references of relevant articles and actual treatment guidelines did not reveal any additional relevant studies. Six references seemed to meet the eligibility criteria and were obtained as full-text papers [13,14,15,16,17,18]. Two studies analyzed the hazards ratio (HR) of patients receiving RT over radical prostatectomy, one only reported HR without 95% CIs, and another included cancers occurring within the first 6 months after the start of the treatment, which were excluded [15,16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, 13 were from the SEER database. One study [19] discussed the effect of radiation in both directions between rectal and prostate cancer.…”
Section: Literature Searchmentioning
confidence: 99%
“…Some authors found that prostate radiation treatment resulted in an increased risk of developing colorectal cancer [12], rectal cancer only [13][14][15][16][17], or colon cancer only [12] while others concluded that there was no association [9,12,18]. Even studies using the Surveillance, Epidemiology, and End Results (SEER) database revealed contradictory results for rectal cancer [8,18,19].…”
Section: Introductionmentioning
confidence: 99%